2017
DOI: 10.1161/strokeaha.116.016275
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban Versus Dabigatran or Warfarin in Real-World Studies of Stroke Prevention in Atrial Fibrillation

Abstract: T he use of oral anticoagulants (OACs), such as the vitamin K antagonists (eg, warfarin), in patients with atrial fibrillation (AF) results in a significant reduction in stroke, ischemic stroke (IS), and systematic thromboembolism (TE), as well as all-cause mortality, when compared with placebo or control.1 However, warfarin has many limitations, including the necessity for regular anticoagulation monitoring, dietary and drug interactions, and the potential for serious bleeding if anticoagulation is poorly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 33 publications
(24 reference statements)
9
84
1
5
Order By: Relevance
“…In our study, rivaroxaban was associated with a higher risk of major bleeding compared with dabigatran or apixaban. The previously discussed American studies and a recently published meta‐analysis also found an increased risk of bleeding associated with rivaroxaban compared with dabigatran . Two Danish studies by Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, rivaroxaban was associated with a higher risk of major bleeding compared with dabigatran or apixaban. The previously discussed American studies and a recently published meta‐analysis also found an increased risk of bleeding associated with rivaroxaban compared with dabigatran . Two Danish studies by Larsen et al .…”
Section: Discussionmentioning
confidence: 99%
“…В недавно проведенном наблюдатель-ном сравнительном "head-to-head" исследовании, в которое был включен 118891 пациент с неклапан-ной ФП в возрасте 65 лет и старше, терапия риваро-ксабаном сопровождалась более высоким риском больших ЖК кровотечений в сравнении с дабигатра-ном в дозе 150 мг 2 раза в день (отношений риска 1,40) [13]. В мета-анализе, проведенном Bai Y, et al, при сравнительном исследовании дабигатрана и ривароксабана установлено, что ЖК кровотечения чаще возникают на фоне применения ривароксабана, причем это различие было характерно как для высо-ких, так и для низких доз сравниваемых препаратов [14]. В проведенном нами исследовании не установ-лено различий в частоте применения НОАК у боль-ных с наличием и отсутствием патологии пищевода, желудка и 12-перстной кишки (17,0% и 19,6%, соот-ветственно).…”
Section: Discussionunclassified
“…In a recent meta-analysis of 17 observational studies comparing rivaroxaban, dabigatran, and warfarin, rivaroxaban was as efficacious as dabigatran for the prevention of stroke or systemic embolism (hazard ratio [HR] 1.02; 95% CI 0.91-1.13), but it was associated with an increased risk of major bleeding (HR 1.38; 95% CI 1.27-1.49), gastrointestinal bleeding (HR 1.33; 95% CI 1.18-1.48), and all-cause mortality (HR 1.23; 95% CI 1.12-1.33) when compared with dabigatran [14]. However, there was no difference between the 2 agents in the risk of acute myocardial infarction or intracranial hemorrhage.…”
Section: Real-world Comparative Evidence For Noacsmentioning
confidence: 99%